2008
DOI: 10.1007/s12072-008-9059-0
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches for treating chronic hepatitis B: when to start, what to start with, and when to stop

Abstract: The natural course of hepatitis B virus (HBV) infection is variable, and chronic hepatitis B (CHB) disease exhibits itself through a spectrum of clinical manifestations. These factors contribute to the challenges faced when managing patients who live with HBV infection. Furthermore, conventional treatment options (e.g., interferon alfa-2a, lamivudine, and adefovir) are moderately effective and can be associated with problems, such as poor tolerability (interferon alfa-2a) and the development of drug resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This further explains why treatment should be considered for people who fall in the immune clearance and immune escape phases as they are more at risk of developing cirrhosis and HCC [5,9,35]. Our study identified 22 and 30 participants in the immune clearance and immune escape phases respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This further explains why treatment should be considered for people who fall in the immune clearance and immune escape phases as they are more at risk of developing cirrhosis and HCC [5,9,35]. Our study identified 22 and 30 participants in the immune clearance and immune escape phases respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Our study showed that participants who were in the immune clearance and immune escape phases had a significantly higher APRI score (most likely to have fibrosis) than those in the other phases. This further explains why treatment should be considered for people who fall in the immune clearance and immune escape phases as they are more at risk of developing cirrhosis and HCC [ 5 , 9 , 35 ]. Our study identified 22 and 30 participants in the immune clearance and immune escape phases respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This response implies that respondents would seek further clinical information before making a definitive decision and it might be speculated that because both patients were older (aged 45 and 55 years), physicians might seek further clarification regarding stage of liver disease (which might be more advanced in older patients). Indeed, liver biopsy is considered a useful element of pretreatment management among patients who do not clearly meet the criteria for starting therapy [25]. Guidelines from the American Association for Study of Liver Disease (AASLD; 2007) [24] recommend that liver histology be considered in patients older than 40 years who have fluctuating or minimally increasing ALT levels.…”
Section: Discussionmentioning
confidence: 99%
“…Buster and Janssen [ 22 ] reported HBV treatment response of 19-35% by administration of peg-IFN. However, administration of pegylated interferon-α 2a for 4 months failed to treat the HBV, HDV and HCV co-infection in Pakistani population [ 20 ] and is associated with adverse effects like depression, flu-like symptoms, neuropsychiatric disorders and suppression of bone marrow [ 28 ].…”
Section: Anti Viral Efficacy Of Peg-interferonmentioning
confidence: 99%